Reflective Practice: How the World Bank Explored Its Own Biases? - Martin McKee; David Stuckler (Kerman University of Medical Sciences, 2016)
While many international organisations have independent evaluations, including the International Monetary Fund (IMF) and World Health organization (WHO), uniquely the World Bank in its 2015 World Development Report sought to ascertain the potential biases that influence how its staff interpret evidence and influence policy. Here, we describe the World Bank's study design, including experiments to ascertain the impact on Bank staff's judgements of complexity, confirmation bias, sunk cost bias, and an understanding of the wishes of those whom they seek to help. We then review the Bank's proposed mechanisms to minimise the impact of the biases they identified. We argue that this approach, that we refer to as 'reflective practice,' deserves to be adopted more widely among institutions that seek to use evidence from research to inform policy and practice.